1988
DOI: 10.1002/jcp.1041350318
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of murine plasmacytoma transferrin receptor expression and G1 traversal by plasmacytoma cell growthfactor

Abstract: Many plasmacytomas arising in BALB/c mice require a specific, macrophage-derived growth factor in order to proliferate in vitro. Since transferrin receptor expression is normally regulated by tissue-specific growth factors and because expression of these receptors is required for cell proliferation, we examined the interaction of plasmacytoma growth factor (PCT-GF) on transferrin receptor expression and cell cycle progression in several PCT-GF-dependent and independent plasmacytoma cell lines maintained in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although the 3 plasmacy toma lines examined took from 16 to 48 h to maximally synchronize in G|, they each took the same amount of time to return to S phase following readdition of IL-6 ( fig. 3), supporting the concept that, whatever the partic ular steady-state level of surface transferrin receptor expression, a uniform, low level receptor number can support growth [5].…”
Section: Role Of Transferrin Receptors In B Lymphocyte Proliferationmentioning
confidence: 64%
See 3 more Smart Citations
“…Although the 3 plasmacy toma lines examined took from 16 to 48 h to maximally synchronize in G|, they each took the same amount of time to return to S phase following readdition of IL-6 ( fig. 3), supporting the concept that, whatever the partic ular steady-state level of surface transferrin receptor expression, a uniform, low level receptor number can support growth [5].…”
Section: Role Of Transferrin Receptors In B Lymphocyte Proliferationmentioning
confidence: 64%
“…How ever, the majority of these cells are dependent on IL-6 for growth. We have characterized the relationship in these cells between IL-6 and transferrin receptor expres sion and have found that, analogous to the IL-2 depen dence of receptor expression in T cells, in IL-6-dependent plasmacytomas transferrin receptor expression re quires the presence of IL-6 [5], Removal of this growth factor leads to a rapid arrest of cells in the Gi phase of the cell cycle and a concomitant loss of transferrin recep tor expression. The time required for G| arrest to be come maximal correlates closely to the initial level of surface transferrin receptors and its rate of decay follow ing removal of IL-6 ( fig.…”
Section: Role Of Transferrin Receptors In B Lymphocyte Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6-dependent 1 cell lines can be established from early transplant generations of these tumors if IL-6 is included in the culture medium (3). In the absence of IL-6, these cell lines arrest in the G 1 phase of the cell cycle and eventually die (4). One such line, T1165, dies within 24 h in the absence of IL-6 but re-enters the S phase in 8 -10 h if restimulated before cell death.…”
mentioning
confidence: 99%